THE INFLUENCE OF LEADERSHIP STYLE AND ORGANIZATIONAL CULTURE ON EMPLOYEE PERFORMANCE MODERATED BY JOB SATISFACTION - Rusman Ariyanto (Jurnal Manajemen, 2024)
This research aims to determine the influence of leadership style and organizational culture on employee performance moderated by job satisfaction at PT Astra Internasional Tbk TSO Auto 2000 Plaju Palembang branch. This research uses a quantitative approach with the aim of explaining the position of the variables studied and the relationship between one variable and another. This research is intended to test hypotheses that have been previously formulated. The results of this research will explain the causal relationship between variables through hypothesis testing. In this research, the analysis method used is path analysis with path analysis using the SmartPLS program.The results of this research found that 1) There is an influence of leadership style on employee performance 2) There is an influence of organizational culture on employee performance 3) There is an influence of job satisfaction on employee performance 4) The moderating role of job satisfactioninfluences leadership style on employee performance 5) The moderating role Job satisfactioninfluences organizational culture on employee performance.